Development of an Illustrated Storybook for Instilling the Value of Apologizing Character in Early Childhood - Utami, Sherly Nur; Rohmah, Naili (FKIP - Universitas Riau, 2025)
The lack of variety in the use of learning media has an impact on the monotonous learning process. This condition causes early childhood to have difficulty in understanding the important meaning of apologies. As a result, the application of character values is less than optimal. This research aims to create and develop picture storybooks as learning media that can help instill the habit of apology in children from an early age. This illustrated storybook product is made using Photoshop application. The research method used is the research and development (R&D) approach with the 4D development model, the 4D research stages include defining, designing, developing, disseminating. Due to time constraints, this research was limited to the development phase. Data analysis is based on the feasibility evaluation scores of picture storybooks given by material experts and media experts as assessors. The results of the feasibility test conducted by material experts and media experts show that the level of material feasibility with an average percentage of 85% with the criteria